DEM investigation of shear flows of binary mixtures of non-spherical particles. (20th July 2019) - Yang, Jiecheng; Guo, Yu; Buettner, Kevin E.; Curtis, Jennifer S.
Highlights: Binary configurations affect the alignment of large particles. Effect of solid fraction ratio is scaled by the root-mean-cubed diameter. Effect of particle shape is minimized by increasing solid fraction of small spheres. A modified kinetic theory for binary non-spherical systems is proposed. Abstract: Discrete element method (DEM) simulations of shear flows of binary mixtures of large non-spherical glued-sphere particles and small spheres are conducted in order to investigate the effect of particle shape and solid volume fraction ratio on the behavior of binary granular flows. The shear stresses first decrease and then increase with total solid volume fraction. The shear stresses increase with the increasing solid volume fraction ratio of large particles. The orientation distributions of large particles show that, in dense regions, the binary system with a higher solid fraction ratio of small spheres exhibits a more uniform alignment in the shear flow direction for large particles. By incorporating the effective particle projected area in the plane perpendicular to the flow plane, the conventional kinetic theory for binary spherical systems is found capable of predicting the stresses for binary systems of non-spherical particles. Stresses for binary systems with various solid volume fraction ratios collapse into a single line by further incorporating the root-mean-cubed diameter, but this scaling is not adequate for dense flows. Comparing the shear stresses for different large particle shapes shows that shear stresses can be affected by the particle shape and particle aspect ratio, but the differences between different particle shapes and aspect ratios are minimized by increasing the solid volume fraction ratio of small spheres.